2015
DOI: 10.1039/c5ra01548k
|View full text |Cite
|
Sign up to set email alerts
|

Continuous catalytic upgrading of fast pyrolysis oil using iron oxides in red mud

Abstract: A catalyst composed primarily of magnetite prepared from red mud via H2 reduction at 300 °C, simultaneously reduced acidity, allowed recovery of carbon, and generated upgradable intermediates from the aqueous fraction of fast pyrolysis oil in a “continuous” process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…Other attractive feature of the upgraded bio-oil collected after short reaction time (0.5 h) is its high content of ketones, mainly acetone (26 % at 400 ºC and 37 % at 500 ºC), 2-butanone (11-19 %) and cyclopentanones (17-30 %). This result suggests that the dolomite has great activity for ketonization of bio-oil oxygenates, through pathways similar to those proposed using a wide variety of catalysts for upgrading pyrolysis oils [27,29,30,40]. Also noteworthy is the presence of 7.3 % of aliphatic hydrocarbons (composed of linear C6-C12 alkenes and C8 cycloalkenes) in the upgraded bio-oil obtained at 500 ºC.…”
Section: Liquid Product Compositionsupporting
confidence: 63%
See 2 more Smart Citations
“…Other attractive feature of the upgraded bio-oil collected after short reaction time (0.5 h) is its high content of ketones, mainly acetone (26 % at 400 ºC and 37 % at 500 ºC), 2-butanone (11-19 %) and cyclopentanones (17-30 %). This result suggests that the dolomite has great activity for ketonization of bio-oil oxygenates, through pathways similar to those proposed using a wide variety of catalysts for upgrading pyrolysis oils [27,29,30,40]. Also noteworthy is the presence of 7.3 % of aliphatic hydrocarbons (composed of linear C6-C12 alkenes and C8 cycloalkenes) in the upgraded bio-oil obtained at 500 ºC.…”
Section: Liquid Product Compositionsupporting
confidence: 63%
“…8). It should be noted that these reactions are promoted by the high concentration of water in the reaction medium [29,48,49], and also by the H2 coming from the dolomite activity for SR and WGS reactions (Eqs. ( 9)-( 10)).…”
Section: Reaction Pathways In Raw Bio-oil Upgradingmentioning
confidence: 99%
See 1 more Smart Citation
“…The total mass decrease can be explained by oxidation of the reduced phases generated by the reaction of RM7 and methane. 13 In this study, the slight increase can be attributed to oxidation of magnetite produced from precursor hematite or goethite phases. It is known that magnetite can be oxidized below 400 o C. 25 From 2 hours reaction time onwards, the carbon species were oxidized in two stages, which may mean that two different carbon species were generated during the methanol cracking process.…”
Section: Resultsmentioning
confidence: 99%
“…Red mud has been investigated for various applications, such as construction materials, [6][7] production of ceramics, 8 gas and water purification, 4,9-10 and catalysis. [11][12][13] Recent studies have demonstrated that red mud is catalytically active to produce carbon from different sources, such as methane, [14][15] ethylene, 16 ethanol, [17][18] associated petroleum gas, 19 and a crude untreated waste stream from bio-diesel production. 20 The resultant carbon materials can be used as functional materials, such as for treatment of metal-contaminated water, 21 whilst the co-product of hydrogen formed in the cracking of hydrocarbons can be used as fuel.…”
mentioning
confidence: 99%